2018
DOI: 10.3390/en11061436
|View full text |Cite
|
Sign up to set email alerts
|

An Adaptive Frequency Strategy for Variable Speed Wind Turbines: Application to High Wind Integration Into Power Systems

Abstract: This paper presents a new frequency controller for variable speed wind turbines connected to the grid under power imbalance conditions. It is based on the fast power reserve emulation technique, having two different operation modes: overproduction and recovery mode. In the first mode, the active power provided by wind turbines is set over the mechanical power, reducing their rotational speed. This overproduction power is estimated according to the frequency excursion. In the second mode, the active power is es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 28 publications
0
33
0
Order By: Relevance
“…Another study uses the fast power reserve emulation. Constant overproduction power is released from the kinetic energy stored in the rotating mass of the wind turbine, with the rotational speed being recovered later through an underproduction period [17,20,21,25,47,61].…”
Section: Improving Frequency Control Strategy Of Wind Turbinesmentioning
confidence: 99%
See 2 more Smart Citations
“…Another study uses the fast power reserve emulation. Constant overproduction power is released from the kinetic energy stored in the rotating mass of the wind turbine, with the rotational speed being recovered later through an underproduction period [17,20,21,25,47,61].…”
Section: Improving Frequency Control Strategy Of Wind Turbinesmentioning
confidence: 99%
“…It is based on supplying the kinetic energy stored in the rotating masses to the grid as an additional active power, being subsequently recovered through an under-production period (recovery) [17][18][19]. Different studies can be found to discuss the definition of overproduction period and the transition from overproduction to recovery period [20][21][22][23][24][25]. These studies are mainly focused on analyzing the inertia reduction problem on isolated power systems [20,21,[23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…RES include bioenergy, geothermal energy, hydropower, ocean energy (tide and wave), PV, thermal solar energy and wind energy (onshore and offshore) [21]. Some of them (such as wind and solar installations) are connected to the grid through power electronic converters, reducing the rotational inertia of the system as they replace conventional generation units [22,23]. This fact compromises the frequency stability and alters the transient response [24].…”
Section: Introductionmentioning
confidence: 99%
“…Wind turbine systems, which now represent a mature technology, have had much more development with respect to other energy conversion systems, e.g., for biomass, solar, and hydropower [1]. In particular, hydroelectric plants present interesting energy conversion potentials, with commonalities and contrast with respect to wind turbine installations [2][3][4].…”
Section: Introductionmentioning
confidence: 99%